Between Diversity and Disorder Trans Identities Reconsidered - Ezra Iskandar; Samuel Soegiarto (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
Transgender communities perceive Christians as oppressive, intolerant, and obsolete, especially when the latter condemns them. Transgender, loosely defined, is a person who feels that [her] gender identity does not conform to [her] sex assigned at birth. This experience can also be called gender identity disorder (GID). Few transgenders decide to go as far as undergoing sex reassignment surgery and hormone therapy. This paper seeks to explore the concepts of transgender identity by offering comparison to the concepts of transability. Transability, loosely defined, is a person who feels that her disabled identity does not conform to her able-physical body. This can also be called Body Integrity Identity Disorder (BIID). A transabled person, for example, feels that she is a limp—having limp identity—despite having normally healthy legs. Few transabled individuals decide to go as far as undergoing amputation. This paper, incorporating theological perspective on the sanctity of human body and philosophical considerations of bodily integrity, invites us to come up with a consistent ethical stance that either acknowledges both (GID and BIID) as expressions of diversity or rejects both (GID and BIID) as forms of disorder.